Two Iteration Methods for Solving Linear Algebraic Systems with Low Order Matrix $A$ and High Order Matrix $B:Y=(A \otimes B)Y+Φ$ (Journal of Computational Mathematics, 2000)
This paper presents optimum a one-parameter iteration (OOPI) method and a multi-parameter iteration direct (MPID) method for efficiently solving linear algebraic systems with low order matrix $A$ and high order matrix $B: Y = (A \otimes B)Y+Φ$. On parallel computers (also on serial computer) the former will be efficient, even very efficient under certain conditions, the latter will be universally very efficient.